Korelasi Skid Resistance dengan Kedalaman Tekstur pada Permukaan Perkerasan Lentur - Pandia, Indra Jaya; Lubis, Adina Sari; Rambe, Andy Putra (Department of Civil Engineering, Diponegoro University, 2016)
Skid Resistance is the force generated between the pavement surface and vehicle’s tires to resist the vehicle advance motion when braking. In this research the correlation between skid resistance value and texture depth on the pavement surface will be determined. The skid resistance value determined by using the British Pendulum Tester (BPT) and to determine the texture depth used Sand Patch Method. The research is conducted directly on a macro textured surface with two methods. The first method is applied on Ngumban Surbakti Road where the samples tested with the same distance from the edge of the pavement along the road; The second method is applied on Jend. Sudirman Road where the samples tested with specific distances from the edge of the pavement until the median. From the results of the analysis, there are some conclusions: (1) there is a positive correlation between the texture depth and skid resistance with a coefficient of determination (R2) = 0.028 on Ngumban Surbakti Road and (R2) = 0.191 on Jend. Sudirman Road;(2) the increase of skid resistance value is directly proportional to the increase of surface texture depth value; and (3) the different methods did not cause significant yield differences.